The role of physical activity in bone metabolism and osteoporosis prevention - Dalz, Monika; Śliwicka, Ewa; Huta-Osiecka, Anna; Nowak, Alicja (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The attainment of peak bone mass in childhood and early adolescence can be ensured by proper diet, which includes a high intake of calcium and vitamin D, and by an adequate level of physical activity. During the period of skeletal involution physical exercise can reduce the rate of bone resorption, and improve motor coordination and prevention of falls. Aim of Study. The aim of the review is to discuss present-day views regarding the effects of physical activity on bone metabolism, and in particular, on osteoporosis prevention. Authors studying the effects of physical activity on bone tissue often classify physical exercises according to the volume of mechanical loads related to gravity and muscle strength. The reaction of bone tissue to mechanical loading depends on the frequency and intensity of the loads. Different forms of physical activity can be classified into weight-bearing, in which the athlete’s skeleton is loaded by the athlete’s own body weight, and non-weight-bearing. The forces acting on bone tissue in result of muscle contractions may additionally affect bone metabolism in loaded sites, and the resulting bone deformations inhibit resorption during bone remodeling. At later stages of life, prevention of falls becomes highly significant, that is why physical exercise should be aimed at the development of mass and muscle strength. In recent years there has been a growing interest in the role of vitamin D in proper bone mineralization and regulation of muscle strength and functional state of muscles. The intake of sufficient levels of vitamin D significantly lowers the risk of falls. Conclusion. Physical activity is a very important determinant of proper bone metabolism, both in pubescence and during skeletal involution. Physical activity is also conducive to the maintenance of muscle mass, which is an important element of osteoporosis prevention. Due to the crucial role of vitamin D in maintaining the proper condition of the musculoskeletal system various forms of outdoor physical activity are highly recommended.
Keywords: bone; physical activity; vitamin D